Student Career Management Model at Vocational Health Education Level for the Work Industry - Nisa, Arofatin; Riyanto, Yatim; Soedjarwo, Soedjarwo (Indonesia Emerging Literacy Education, 2025)
Objective: This study aims to develop a career management model for students of Health vocational high schools in the workforce. Method: This study uses a descriptive method with a case study approach. The research objects are Nusantara Health Vocational High School and Surabaya Health Vocational High School. The research instruments are in-depth interview guides, observation guides, and documentation guides. The analysis uses multi-site analysis. Results: The results of the study found that the career management model for students of Health vocational high schools consists of 4 stages, namely 1) career management planning consisting of annual work meetings, involving the work industry in learning planning, and curriculum modification planning according to the needs of the work industry; 2) organizing career management consisting of dividing tasks and responsibilities based on areas of expertise, determining and confirming those responsible for each program, and determining coordination and integration paths between sections; 3) implementation of career management; and 4) career management supervision consisting of comprehensive supervision in all aspects, use of monitoring and evaluation instruments, involvement of alumni and the world of work in the monitoring and evaluation process. Novelty: This model uniquely incorporates active industry participation in curriculum design, field practice implementation, and alumni-involved evaluation while introducing a holistic structural coordination framework and integrated monitoring tools rarely applied in health vocational education contexts.